Hormonal induction of spermiation in the common eastern froglet: testing alternative routes of hormone administration - Anastas, Zara M.; Byrne, Phillip G.; Silla, Aimee J. (Frontiers in Amphibian and Reptile Science, 2025)
Application of hormone therapies to amphibians has increased substantially in recent years, though protocol development has predominantly focused on moderate- to large- bodied species, with fewer examples of application to small- or micro- bodied amphibians. The development of alternative methods of hormone administration that circumvent the need for animal injection stand to increase the diversity of species to benefit from hormone therapy, particularly species of smaller body size. The aim of the present study was to quantify the efficacy of different routes of hormone administration of gonadotropin releasing-hormone agonist (GnRHa) on spermiation in the common eastern froglet, Crinia signifera. Males were assigned to one of four experimental treatments; intranasal application, hormone injection, hormone bath or no hormone, and sperm-release was quantified (males spermiating, total sperm, sperm concentration and sperm viability) at 0, 2, 4, 6, 8, 10, and 12-hours. Sperm-release was highest in the hormone injection and hormone bath treatments, both resulting in 88% of males spermiating, and the highest mean total number and concentration of sperm. Intranasal application resulted in poor sperm-release, with only 25% of males spermiating, and very low total sperm and sperm concentration, statistically similar to the aspermic no-hormone treatment group. Sperm viability remained above 86% and did not differ significantly among treatments. Overall, we describe successful protocols for the hormonal induction of sperm-release in C. signifera. Our findings add to a growing body of evidence that topical hormone application offers a viable alternative to injection for amphibians, providing an effective pathway for the increased application of hormone therapies to small-bodied amphibian species.